Kompetensi pengurusan ketua-ketua panitia matapelajaran di sekolah-sekolah menengah di bahagian Kuching/Samarahan : satu tinjauan - Dayang Normala, Binti Abang Bohari (2000)
This survey is conducted to verify levels of management competencies of head subject department and management competencies needed in managing their department. This survey also tries to determine whether there are differences between levels of management competencies in five categories of competencies (Department Administration, Curriculum Development, Supervision and Instruction, Profesionalisme Development and Interpersonal Relationship) and demographic characteristics of respondent. This survey also tries to determine whether there are relationships between levels of management competencies and management competencies needed by the respondent.